2014
DOI: 10.7567/jjap.53.03dd02
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polymer layer formation during SiO2/SiN etching by fluoro/hydrofluorocarbon plasmas

Abstract: In reactive-ion etching (RIE) of silicon oxide (SiO2) or silicon nitride (SiN) by fluorocarbon (FC) or hydrofluorocarbon (HFC) plasmas, fluorinated carbon layers may be formed on the etched surfaces and affect their etching rates. In this study, the properties of SiO2 and SiN etching by FC or HFC plasmas are examined in light of the formation mechanism of such carbon layers by molecular dynamics (MD) simulation. Furthermore, in this study, the electronegativity effect of fluorine (F) is taken into account in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Under the ion bombardment conditions examined in this study, essential collision dynamics, such as penetration or reflection of the incident ion and dislocation of Si atoms following the ion impact, takes place within the first 700 fs of each simulation cycle. The latter 300 fs cooling simulation 23,[26][27][28] is meant to emulate a natural relaxation process of the surface, which would typically ensue for micro-or milliseconds in reality, before another ion incidence occurs in the same neighboring area (represented by the surface area of the model substrate). Ions used in the simulations are H þ and Ar þ , with incident ion energies in the range from 100 to 500 eV and incident ion angles from 0 (normal incidence) to 80 .…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Under the ion bombardment conditions examined in this study, essential collision dynamics, such as penetration or reflection of the incident ion and dislocation of Si atoms following the ion impact, takes place within the first 700 fs of each simulation cycle. The latter 300 fs cooling simulation 23,[26][27][28] is meant to emulate a natural relaxation process of the surface, which would typically ensue for micro-or milliseconds in reality, before another ion incidence occurs in the same neighboring area (represented by the surface area of the model substrate). Ions used in the simulations are H þ and Ar þ , with incident ion energies in the range from 100 to 500 eV and incident ion angles from 0 (normal incidence) to 80 .…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The addition of H 2 or O 2 gas in PFC plasmas has been widely employed to control the etching characteristics; while H atoms generated through the dissociation of H 2 in plasma act as a scavenger for F atoms, thereby lowering etch rates and increasing SiO 2 -to-Si selectivity, O atoms from O 2 dissociation consume C atoms on the material surfaces, reducing the formation of FC films [ 9 ]. Following the same mechanism as H 2 /O 2 addition, hydrofluorocarbon gases (HFC, CH x F 4−x with x = 1, 2, or 3) with H atoms in their molecular structures instead of F atoms are frequently adopted, and numerous studies on the mixture of PFC and HFC precursors have been reported over the years [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] This is because FC is known to react with SiO 2 and form volatile species. Similarly, because hydrofluorocarbon (HFC) plasmas are widely used for reactive ion etching (RIE) of silicon nitride (SiN) with high selectivity over Si and SiO 2 , [42][43][44][45] HFC plasmas are also used in the adsorption step for PE-ALE of SiN. 9,40,[46][47][48][49][50][51][52] HFC plasmas is also used in the PE-ALE adsorption step of SiN.…”
Section: Introductionmentioning
confidence: 99%